Publikasi Letter to Editor untuk Menghidupkan Dialog Akademik (Editorial) - Suparji, Suparji (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2025)
The "Letter to Editor" section in the 2-TRIK: Tunas-Tunas Riset Kesehatan journal provides a reflective and critical space for academics, practitioners, and general readers to participate in scientific discourse. This article reviews the definitions, principles, and relevant content of Letter to Editor writing, highlighting its strategic benefits for academic and institutional capacity building. With an inclusive and evidence-based editorial approach, 2-TRIK encourages responsive, corrective, and constructive contributions to published articles and current issues in the health sector. This closing article emphasizes the importance of Letter to Editor as a medium for democratizing knowledge and strengthening academic culture.Keywords: letter to editor; scientific publication; academic communication; health editorialABSTRAK Rubrik "Letter to Editor" dalam jurnal 2-TRIK: Tunas-Tunas Riset Kesehatan membuka ruang reflektif dan kritis bagi akademisi, praktisi, dan pembaca umum untuk berpartisipasi dalam diskursus ilmiah. Artikel ini mengulas definisi, prinsip, dan konten yang relevan dalam penulisan Letter to Editor, serta menyoroti manfaat strategisnya bagi pengembangan kapasitas akademik dan institusional. Dengan pendekatan editorial yang inklusif dan berbasis bukti, 2-TRIK mendorong kontribusi yang bersifat responsif, korektif, dan konstruktif terhadap artikel-artikel yang telah diterbitkan maupun isu-isu aktual dalam bidang kesehatan. Penutup artikel ini menegaskan pentingnya Letter to Editor sebagai medium demokratisasi pengetahuan dan penguatan budaya akademik.Kata kunci: letter to editor; publikasi ilmiah; komunikasi akademik; editorial kesehatan